2019
DOI: 10.1021/acs.iecr.8b06151
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Potassium Hydrogen Carbonate: Thermochemistry, Kinetics, and Textural Changes in Solids

Abstract: To determine unbiased rates of the decomposition of KHCO 3 , slowly increasing-and constant-temperature TGA methods were employed with small, finely ground samples. Such reaction provides a novel, porous, and highly reactive sorbent for noxious and/or malodorous gases. The bicarbonate commences decomposing at 364 K, and the maximum rate of reaction, attained at 421.9 K, amounts to 5.73 × 10 −4 1/s. Taking advantage of the Schlomilch function, an Arrhenius-type relationship is developed by an integral method: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 43 publications
(89 reference statements)
0
13
1
Order By: Relevance
“…The previously‐mentioned results are quite different from those obtained by M. Hartman et al., [16] who showed that the transformation of KHCO3 into normalK2CO3 occurred in a single step at 91 °C, proved the strong interaction between LCDC and KHCO3 . The small sharp endothermic peak is indicated by a blue circle around 910 °C without gain or loss of mass in TG plot corresponding to the beginning melting of normalK2CO3 [16] . Based on DTA/TG investigations, the precipitate LCDC@KHC was calcined at temperature below 120 °C and the sintering procedure was restricted to<900 °C.…”
Section: Resultscontrasting
confidence: 77%
“…The previously‐mentioned results are quite different from those obtained by M. Hartman et al., [16] who showed that the transformation of KHCO3 into normalK2CO3 occurred in a single step at 91 °C, proved the strong interaction between LCDC and KHCO3 . The small sharp endothermic peak is indicated by a blue circle around 910 °C without gain or loss of mass in TG plot corresponding to the beginning melting of normalK2CO3 [16] . Based on DTA/TG investigations, the precipitate LCDC@KHC was calcined at temperature below 120 °C and the sintering procedure was restricted to<900 °C.…”
Section: Resultscontrasting
confidence: 77%
“…Thereafter, temperature‐programmed reduction (TPR) was carried out on red mud and 2 wt % K‐promoted red mud (Figure S10). Several differences could be observed upon comparing both samples: i) peaks below 120 °C for the K‐promoted sample, which arise from the decomposition of KHCO 3 that starts at 67 °C; ii) peaks in the region of approximately 370–730 °C, which come from the reduction of iron species: hematite (Fe 2 O 3 ) into magnetite (Fe 3 O 4 ) at 420 °C (vs. 450 °C for the promoted sample), broad reduction of magnetite to iron monoxide at 510–720 °C (vs. 530–730 °C for the promoted sample), and reduction to metallic Fe at 750 °C . In accordance with previously reported results, the addition of K shifts the reduction temperature of iron oxide species to higher temperatures .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the large differences in the specific surface areas of the upgraded ACs impregnated with KOH and K 2 CO 3 , as shown in Figure 3, are difficult to explain. Because KHCO 3 also transforms into K 2 CO 3 at temperatures greater than 140 • C (2KHCO 3(s) K 2 CO 3(s) + H 2 O (g) + CO 2(g) ) [25], the amounts of K 2 CO 3 formed on the carbon precursors would adversely affect the degree of activation. Given that the peaks of K 4 H 2 (CO 3 ) 3 and KHCO 3 are more intense for the carbon precursor impregnated with K 2 CO 3 that for that impregnated with KOH, the K 2 CO 3 -impregnated sample would favor the formation of K 2 CO 3 during activation.…”
Section: Xrd Resultsmentioning
confidence: 99%